Communication in the teaching, learning and professional activity of the Mathematics teacher: implications of Professional Didactics (DP) - Vieira Alves, Francisco Regis; Acioly-Régnier, Nadja Maria (IE Revista de Investigación Educativa de la REDIECH, 2021)
This paper presents a discussion about communication, its strategic relevance in teaching as well as learning, however, emphasizing the role and activity of the Mathematics teacher. In fact, we report several works in Brazil that address the communicative interactions necessary for the transmission of mathematical knowledge, however, little is mentioned about the Mathematics teacher’s learning, in face of professional situations and the acquisition of appropriate skills for a meaningful exchange of interactions. Thus, certain assumptions and an analysis bias supported by the French research of Professional Didactics (PD), the paper discusses the notion of professional competence of the teacher and the use of professional gestures which are essential for the performance of any work activity. Finally, there is an example related to the teaching of Mathematics, regarding the notion of generalized integral, in which communicative interactions are conditioned by interaction with technology and software use and the occurrence of gestures that carry and convey the meaning of mathematical scientific concepts.